Die pollenanalytische Datierung von jüngeren Vulkanausbrüchen - Straka, Herbert (ERDKUNDE, 1956)
During the last few years pollen analysis has gained increasing importance for the dating of recent volcanic eruptions; on the other hand it has also become possible to use volcanic ruff and ash, which were spread over !arge areas and form horizons in peat and silt deposits of former lakes, as a means of establishing links over great distances between contemporary volcanic deposits. The absolute date of volcanic eruptions has been established more precisely in a number of cases by the radio-carbon method, and earlier datings made by pollen analysis have been confirmed by that method. In the first section of this paper an attempt is made to illustrate the method of dating volcanic strata by means of pollen analysis using the Eifel maare as an example. Then follows a section on the absolute dating and the importance of the dating of the volcanic eruption in the Eifel mountains. In conclusion a review is given of pollen analytical dating of volcanic eruptions in other parts of the world, in particular in Iceland, Patagonia and the Cordillera regions of North America. The appended bibliography is as comprehensive as possible.